2004
DOI: 10.1785/0120030219
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Strong Ground-Motion Simulation of the 7 September 1999 Athens (Greece) Earthquake

Abstract: The stochastic method for finite faults is applied to simulate strong ground motion from the 7 September 1999, moment magnitude M 5.9 Athens earthquake. The method includes descritization of the fault plane into a certain number of subfaults, each of which is assigned an x ‫2מ‬ spectrum. A slip-distribution model, derived from previous studies of this earthquake, is used to specifically account for the source effect. Contributions from all subfaults are then empirically attenuated to the observation sites, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…It has also been adopted in several studies of earthquakes in the broader Aegean area (e.g. Benetatos and Kiratzi 2004;Karastathis et al 2010;Margaris and Boore 1998;Mountrakis et al 2012;Roumelioti et al 2004;Theodulidis et al 2006) and is considered as an effective tool, especially in cases where the sparsity of seismological data does not facilitate the application of more refined and physically sound methods.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been adopted in several studies of earthquakes in the broader Aegean area (e.g. Benetatos and Kiratzi 2004;Karastathis et al 2010;Margaris and Boore 1998;Mountrakis et al 2012;Roumelioti et al 2004;Theodulidis et al 2006) and is considered as an effective tool, especially in cases where the sparsity of seismological data does not facilitate the application of more refined and physically sound methods.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies demonstrated the ability of the method to provide reliable estimates of ground motion in various tectonic environments (e.g., Beresnev and Atkinson 1998;Roumelioti et al 2004;Castro et al 2008; Ugurhan and Askan 2010 and references therein).…”
Section: The Methodsmentioning
confidence: 99%
“…We used a stochastic finite-fault model, as proposed by Beresnev and Atkinson (1997), to simulate the near-source strong ground motion in the region of Kalamata. The method has been successfully implemented for the broader Aegean region by various researchers (Margaris and Boore, 1998;Roumelioti et al, 2004;Kassaras et al, 2015, among others).…”
Section: Seismic Hazard Assessmentmentioning
confidence: 99%